Tailoring proton transfer species on the membrane surface: An approach to enhance proton conductivity for polymer electrolyte membrane fuel cell. (16th January 2023) - Pokprasert, Adisak; Chirachanchai, Suwabun
Abstract: The efficiency of proton conductivity in proton exchange membrane (PEM) depends on how proton species can effectively transfer through the membrane either in hydrous system or anhydrous system. Although the incorporation of proton donors and/or acceptors via chemical modification, blending, including preparing composites in polymer solution state before casting the membrane is a general approach, the proton transfer species may not be effectively functioned as they were randomly existed in PEM. As proton transfer initially occurs at the PEM surface, the decoration of the proton transfer species on the surface can be considered as an alternative choice to develop PEM. The surface modifications can be carried out by attaching the functional molecules and/or polymers to favor the proton transfer. The present review summarizes the approaches to construct the PEM surface with proton conductive species, especially via layer-by-layer, and polymer brushes to enhance the PEM performances. Graphical abstract: Image 1 Highlights: Progress and development of PEM from various approaches. Surface modification of polymer electrolyte membrane. Proton transfer in heterocycles based on H-bond and molecular mobility. Proton donor and acceptor through acid and heterocycles. Layer-by-layer and polymer brushes for enhancement of PEM efficiency.